Postglacial colonization history reflects in the genetic structure of natural populations of Festuca rubra in Europe - von Cräutlein M.; Leinonen P.H.; Korpelainen H.; Helander M.; Väre H.; Saikkonen K. (WILEY, 2022)
We conducted a large-scale population genetic survey of genetic diversity of the host grass Festuca rubra s.l., which fitness can be highly dependent on its symbiotic fungus Epichloe festucae, to evaluate genetic variation and population structure across the European range. The 27 studied populations have previously been found to differ in frequencies of occurrence of the symbiotic fungus E. festucae and ploidy levels. As predicted, we found decreased genetic diversity in previously glaciated areas in comparison with nonglaciated regions and discovered three major maternal genetic groups: southern, northeastern, and northwestern Europe. Interestingly, host populations from Greenland were genetically similar to those from the Faroe Islands and Iceland, suggesting gene flow also between those areas. The level of variation among populations within regions is evidently highly dependent on the postglacial colonization history, in particular on the number of independent long-distance seed colonization events. Yet, also anthropogenic effects may have affected the population structure in F. rubra. We did not observe higher fungal infection rates in grass populations with lower levels of genetic variability. In fact, the fungal infection rates of E. festucae in relation to genetic variability of the host populations varied widely among geographical areas, which indicate differences in population histories due to colonization events and possible costs of systemic fungi in harsh environmental conditions. We found that the plants of different ploidy levels are genetically closely related within geographic areas indicating independent formation of polyploids in different maternal lineages.